2008
DOI: 10.1007/s10815-007-9188-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of embryo quality between intracytoplasmic sperm injection and in vitro fertilization in sibling oocytes

Abstract: Background The aim of the present study was to compare the quality of embryos derived from sibling oocytes by in vitro fertilization (IVF) or ICSI. Methods Consecutive patients with a less than 40% fertilization rate in a previous standard IVF cycle or with relative male factor infertility were recruited for the study. The oocytes retrieved from each patient were divided into two groups for either conventional insemination (group A) or ICSI (group B). Power analysis showed that to detect a 25% difference in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 40 publications
(55 reference statements)
4
13
0
Order By: Relevance
“…When this work compared embryo quality and implantation potential from a kinetic point of view, the results demonstrated no significant differences between the IVF and ICSI groups, which is agreement with previous studies (Ruiz et al, 1997;Yoeli et al, 2008), although IVF-derived embryos showed a positive trend in the percentages of optimal embryos with a predicted higher implantation potential. Thus, after controlling for maternal effects, embryo morphokinetic characteristics do not seem to be influenced by the mode of fertilization, so it is possible to assume that embryo quality depends on intrinsic factors of the gametes involved rather than on the fertilization process per se.…”
Section: Discussionsupporting
confidence: 90%
“…When this work compared embryo quality and implantation potential from a kinetic point of view, the results demonstrated no significant differences between the IVF and ICSI groups, which is agreement with previous studies (Ruiz et al, 1997;Yoeli et al, 2008), although IVF-derived embryos showed a positive trend in the percentages of optimal embryos with a predicted higher implantation potential. Thus, after controlling for maternal effects, embryo morphokinetic characteristics do not seem to be influenced by the mode of fertilization, so it is possible to assume that embryo quality depends on intrinsic factors of the gametes involved rather than on the fertilization process per se.…”
Section: Discussionsupporting
confidence: 90%
“…Dumoulin et al (18) demonstrated that embryos obtained after ICSI had a decreased potential to develop into blastocysts. Yoeli et al (19) and our previous report (20,21) also revealed that embryo quality does not seem to be influenced by the mode of fertilization (IVF or ICSI). We may assume that embryo quality depends on intrinsic factors of the gametes involved, rather than on the fertilization process per se.…”
Section: Discussionsupporting
confidence: 72%
“…In patients with very low numbers of oocytes retrieved and non-male factor infertility, conflicting data have been reported, with either significantly higher fertilization rates using ICSI as compared to IVF [32], or similar between the two methods [31]. In both of the above studies, clinical pregnancy, implantation rates, live birth rates, cycle cancellation and early pregnancy loss did not differ between the two fertilization methods [31,32], suggesting that embryo quality does not seem to be affected by the method of fertilization, but rather by the intrinsic quality of the gametes themselves [46].…”
Section: Discussionmentioning
confidence: 89%